2018
DOI: 10.1177/0963689718779346
|View full text |Cite
|
Sign up to set email alerts
|

The impact of in vitro cell culture duration on the maturation of human cardiomyocytes derived from induced pluripotent stem cells of myogenic origin

Abstract: Ischemic heart disease, also known as coronary artery disease (CAD), poses a challenge for regenerative medicine. iPSC technology might lead to a breakthrough due to the possibility of directed cell differentiation delivering a new powerful source of human autologous cardiomyocytes. One of the factors supporting proper cell maturation is in vitro culture duration. In this study, primary human skeletal muscle myoblasts were selected as a myogenic cell type reservoir for genetic iPSC reprogramming. Skeletal musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 59 publications
6
53
0
Order By: Relevance
“…This is in line with results from other studies where extended culture of the CMs also showed enhanced maturation of the cells (23)(24)(25). The difference in response related to time in culture can probably be one explanation of why there is a discrepancy among the data reported previously regarding hypertrophic responses in stem cell-derived CMs (26,27).…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with results from other studies where extended culture of the CMs also showed enhanced maturation of the cells (23)(24)(25). The difference in response related to time in culture can probably be one explanation of why there is a discrepancy among the data reported previously regarding hypertrophic responses in stem cell-derived CMs (26,27).…”
Section: Discussionsupporting
confidence: 90%
“…The advantages of I K1 -enhanced iPSC-CM include the absence of spontaneous beating (and therefore allow the possibility of controlling electrical pacing), and a resting membrane potential close to physiological values (i.e., −80 mV) [167]. Other strategies to improve the maturation of hiPSC-CMs include long term culture [168] and specific biochemical methods such as using the hormone triiodothyronine [169] or fatty acids [170]. The bioengineering approach, which consists of generating engineered three-dimensional human cardiac tissue, and applying electrical stimulation or mechanical strain to improve both structural and functional maturation, shows great promise [171].…”
Section: Limitations Of Using Human Induced Pluripotent Stem Cell-dermentioning
confidence: 99%
“…6C). Additionally, our previously published investigations indicated that extended in vitro cell culture may lead to the improvement of cardiomyocyte maturation parameters, such as sarcomere organization, accumulation of cardiac mitochondrial density and transition from alpha to beta MHC isoform 42 .…”
Section: Discussionmentioning
confidence: 98%